Self-evaluation of memory systems : Development of the questionnaire - Tonković, Mirjana psihologinja; Vranić, Andrea (2011)
Objectives: The term metamemory refers to the knowledge one has about the development and use of memory in general, and one’s own memory processes in particular. The current theoretical perspective on memory processes is best described by the memory systems framework which represents a useful tool in specifying different ‘kinds’ of memory. We present here the Self-evaluation of Memory Systems Questionnaire (SMSQ), which assesses the multidimensional construct of metamemory based on memory systems framework. Method: SMSQ has been developed on a large and heterogeneous sample (N=3088) via both, web-based and paper-and-pencil form. With the aim of increasing its general utility, we used items referring to situations or materials which are highly likely for everyone to have encountered during their everyday life. Results: Analyses revealed good content validity, factorial validity, internal consistency reliability, and construct validity in terms of expected theoretical group differences. SMSQ is represented by 6 distinct factors: subjective evaluation, episodic memory, semantic memory, memory for numbers, visuospatial memory, and reminder and aids. Age differences found on SMSQ between young and old adults confirm the well- established empirical findings on the memory and aging. Conslusion: SMSQ is a brief, easily administrable, multidimensional metamemory questionnaire, marked with the sound background from the findings on memory systems and cognitive aging.
Projekt MZOS
Projekt MZOS
ENG